Relationship Intimacy and Self Disclosure Young Married Couple - Anggia Wahyu Agustin; Asmidir Ilyas (Universitas Negeri Padang, 2019)
This study describing the intimacy husband and wife, describing self disclosure young married couple, and examine the relationship of intimacy with self disclosure young married couple. Type of the research is quantitative descriptive correlational. Research subjects are young age couples who totaled 42 couples. Instruments used for data collection is a likert model scale. Dana analyzed is using percentage and interval. Data analyzed to know the relationships between these two variables used statistical analysis with Pearsons Product Moment Correlations technique and used SPSS For Windows 20.0. The results of this reseach is (1) intimacy husband and wife are in an intimate category, (2) self disclosure husband and wife are in the open category, (3) relationship intimacy with self disclosure young married couple is a significant. Based on finding of research, hopefully the counselor can provide professional assistance with information services and personal counseling to help young couple to enhancing their intimacy and self dislcosure.